Evaluation of PAI Teachers in Online Learning During The Covid-19 Pandemic at SMA Negeri Palu - Erniati, Erniati; Karmawati, Karmawati; Maslan, Maslan (Jurnal Diskursus Islam, 2023)
The sudden online learning policy resulted in teachers experiencing inequality. Therefore, the purpose of this study is to examine the results of teacher evaluation in implementing online learning after the enactment of government policies during the COVID-19 pandemic with the aim of analyzing teacher performance during online learning, then mapping the obstacles faced as consideration in finding solutions for the next implementation of online learning. The method used in this study is qualitative descriptive by collecting observation data, student and teacher survey data through google form and teacher monitoring and evaluation results from school LMS. From the results of the study, it was found that teacher evaluation in online learning was less effective. The reason is the gap in teachers’ digital literacy due to unpreparedness with online learning and the age of teachers so they cannot operate IT or digital applications for online learning.